Larvicidal activity of cassava leaves extract against culex quinquefasciatus, aedes aegypti and anopheles stephensi (Diptera: Culicidae) - VINITA VINJOY JERUSHA,; VINITA VINJOY JERUSHA,; ARULSAMY JEBANESAN, (International Journal of Pharma and Bio Sciences, 2019)
Mosquitoes are an important public health concern as they spread life-threatening diseases such as malaria, filaria, Japanese encephalitis, dengue fever, chikungunya, and yellow fever. In the last decades, synthetic insecticides were extensively used for the control of these vector-borne diseases but it also reported the detrimental side-effects in human beings and pet animals. To overcome the side effects, plants-derived secondary metabolites were screened and tested for insecticidal properties. Plant-derived agents belonging to many families have been reported to possess larvicidal properties against Cx. quenquifasciatus, Ae. aegypti and An. stephensi mosquitoes (Diptera: Culicidae). Larvicidal agents for mosquito larval control are a major module for controlling vector-borne diseases. The present study deals with the insecticidal activity of ethanol extracts of Cassava leaves against Culex quinquefasciatus, Aedes aegypti, and Anopheles stephensi, larvae. Result analysis clearly indicates that ethanol extract of Cassava showed higher potency against Cx. quinquefaciatus and Ae. aegypti as compared to An. stephensi. The phytochemicals or crude extracts derived from plant sources also act as a larvicide against mosquito vectors. The ethanolic extract was found potent Ethanol extract were found significantly lethal to the tested mosquito vectors. The study clearly revealed that Crude extract or isolated bioactive compounds from the plant Cassava could be used in breeding grounds of the mosquitoes and can be used as an alternative against synthetic insecticides.